Perancangan Sistem Informasi Perizinan Tinggal Orang Asing di Indonesia Menggunakan Metode Rapid Application Development (RAD) Berbasis Android (Studi Kasus : PT Bintang Aneka Karya) - Alvin; Fajar Septian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT Bintang Aneka Karya is a service company that provides residence permit services to foreigners who need legal documents to live in Indonesia. The licensing process still uses paper documents and the paper is transferred to Excel. The current system is considered inadequate because it can lead to duplicate data and slow retrieval of data when needed. The purpose of this letter is to help foreigners know what the conditions are for applying for residency in Indonesia.The author made direct observations in her PT Bintang Aneka Karya, as HRD she interviewed Mr. Windu Pranoto directly to explore the issues related to residence permits for foreigners. Results of implementations and tests performed on applications designed for PT Bintang Aneka Karya uses the Rapid Application Development (RAD) method. It helps foreigners to access the information created and facilitate their application and PT Bintang Aneka Karya can store your residency application report data securely as it is stored directly in the database.